ANALISIS PELACAKAN KONTAK ERAT KASUS KONFIRMASI COVID 19 DI WILAYAH KERJA PUSKESMAS HARAPAN RAYA - Christine Vita Gloria Purba; Desri Novita Yanti; Alhidayati Alhidayati; Agus Alamsyah (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
The target of tracing confirmed cases with close contacts has not been achieved in Indonesia, where only 2 provinces have achieved close contact tracing exceeding 10, namely East Java and North Sumatra. Based on an initial survey at the Harapan Raya Health Center, there were 1,329 confirmed cases of Covid 19 with a ratio of close contacts to confirmed cases of only 4 close contacts. This study aims to analyze close contact tracing of confirmed cases of Covid 19 in the Harapan Raya Health Center Work Area. This research is a qualitative research. The informants consisted of the main informants, namely those in charge of surveillance and tracing officers and supporting informants were the heads of the Harapan Raya Health Center and Bhabinkamtibmas. Data were collected using interview guidelines and checklists. Data analysis used source triangulation and method triangulation. The results of the study show that tracing close contacts of the Covid 19 case is a priority and adequate human resources and facilities are available. In the process of carrying out close contact tracing the Covid 19 case has been carried out well, however there are several obstacles such as identification discrepancies, closed cases and close contacts and cases that already consider Covid 19 to be a mild disease so they are not willing to be traced.Keywords : Analysis, Close Contact Tracing, COVID-19 Cases.